The perception of critical thinking and problem solving skill among Malaysian undergraduate students - Rodzalan, Shazaitul Azreen; Mohamed Saat, Maisarah (Elsevier Science Ltd, 2015)
This study aims to investigate students’ perception on their critical thinking and problem solving skill. It also aims to determine whether there are differences between genders and academic disciplines on this skill. A sample of 2000 undergraduate students from six Malaysian public universities completed the survey. Findings indicate that students perceived they have high critical thinking and problem solving skill. It is also revealed that male students are perceived to have better critical thinking and problem solving skill. Social science students appear to perform better in this skill, as compared to science and engineering students.